2015
DOI: 10.1038/srep12242
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the primary lesion apparent diffusion coefficient (ADC) in nasopharyngeal carcinoma: a retrospective study of 541 cases

Abstract: The prognostic value of the primary lesion pretreatment apparent diffusion coefficient (ADC), which is obtained by diffusion-weighted magnetic resonance imaging (MR-DWI), remains unknown in nasopharyngeal carcinoma (NPC). Thus, to investigate whether the pretreatment ADC value as measured from the primary site on MR-DWI is an independent prognostic factor in NPC, we retrospectively reviewed a cohort of 541 patients with histologically-proven stage I-IVB NPC. All patients underwent MRI using a 3-Tesla system (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 44 publications
6
49
2
Order By: Relevance
“…Our study broadly supports the findings of Zhang et al, 15 with high primary tumor ADC values being associated with poor local response. However, we were unable to show this correlation by using the ADC mean and could only show such a correlation by using the ADC skewness.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study broadly supports the findings of Zhang et al, 15 with high primary tumor ADC values being associated with poor local response. However, we were unable to show this correlation by using the ADC mean and could only show such a correlation by using the ADC skewness.…”
Section: Discussionsupporting
confidence: 82%
“…[12][13][14] These 3 studies showed mixed results with both low [12][13] and high 14 pretreatment ADCs reported in tumors with poor outcomes, with the results being significant in only 1 of the studies. 12 However, a recent NPC study by Zhang et al 15 with long-term follow-up and a large sample size of 541 patients showed a significant association between a high mean ADC in primary tumors pretreatment and poor survival at 3 years. That study measured the pretreatment mean ADC at the level of the largest primary tumor diameter and used ROC curve analysis to identify an optimal cutoff ADC for LF of Ն0.747 ϫ 10 Ϫ3 mm 2 /s (area under the ROC curve ϭ 0.68, P ϭ .004), which was shown to correlate with both local relapse-free survival and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of nasopharyngeal carcinoma is mainly located at the top and lateral wall of nasopharynx, relatively hidden, when the early onset of symptoms is not obvious, or lack of specificity, and is easy to be ignored by the patients. And the vast majority of poorly differentiated nasopharyngeal carcinoma, malignant degree is high, easy early cervical lymph node and distant metastases, most patients were advanced nasopharyngeal car-cinoma on symptoms or when they see a doctor [2]. Nasopharyngeal carcinoma is generally sensitive to radiotherapy.…”
Section: Introductionmentioning
confidence: 99%